Perlindungan Hukum bagi Konsumen dalam Pembelian Rumah KPR Secara Oper Kredit Tanpa Diketahui oleh Pihak Bank - Verawati, Desi; Tondy, Cicilia Julyani; Widyanti, Amelia Nur (Universitas Islam Negeri Alauddin Makassar, 2024)
The process of buying a house through a Home Ownership Credit all the time is always met with obstacles in installment payments, so that the buyer is in default because he does not pay the installments according to the agreement signed between the buyer and the bank. The formulation of this research problem is what are the legal consequences of the transfer of the purchase and sale of the object of home ownership credit guarantee in a credit pass transaction without the knowledge of the bank and how is the legal protection for consumers in the purchase and sale of home loan guarantee objects in a credit pass transaction without the knowledge of the bank. The theories used in this study are according to Moch, Ismaeni, Legal Protection Theory, Civil Contract Theory according to Sudikno Mertokusumo. The method used in this study is normative juridical (research on literature law or secondary data with sources of primary, secondary and tertiary legal materials). The research approach used is a legal, case, analytical approach and a conceptual approach with legal material collection techniques carried out by identifying and inventorying legal rules, book literature, and other legal materials. The technique of analyzing legal materials is carried out by grammatical legal interpretation and systematic interpretation. From the research, it was concluded that the transfer of home loans without the knowledge of the bank as a creditor before the credit is paid off is an act that should not be done by the debtor. The impact of this action is the emergence of risks to the debtor who accepts and sullito to take a certificate for the new debtor and in the credit over.